Validation of new combinations in the lichen genus Lecanoropsis (Lecanoraceae) - Ivanovich, Cristóbal; Weber, Lilith; Palice, Zdeněk; Hollinger, Jason; Otte, Volker; Sohrabi, Mohammad; Sheehy, Steve; Printzen, Christian (Phytotaxa, 2025)
N/A